Drought tolerance selection of GT1 rubber seedlings with the addition of polyethylene glycol (PEG) 6000 - SYARIFAH AINI PASARIBU; Mohammad Basyuni; EDISON PURBA; YAYA HASANAH (Society for Indonesian Biodiversity, 2021)
Abstract. Pasaribu SA, Basyuni M, Purba E, Hasanah Y. 2021. Drought tolerance selection of GT1 rubber seedlings with the addition of polyethylene glycol (PEG) 6000. Biodiversitas 22: 394-400. Tolerance of the rootstock of rubber to drought stress is not optimal. The root system can therefore be used as an indicator of drought tolerance to inhibit the growth of the plant. A good root system of rubber rootstocks is thought to help the plants acquire greater resistance to drought stress. Polyethylene glycol 6000 osmotic solution controls the water potential in the growing medium. This study aimed to analyze the effect of PEG 6000 osmotic solution (0%; 7.5%; and 15% concentration) on rubber seedlings leading to the development of morphological characters and sensitivity index. GT1 (Gondang Tapen 1) rubber seeds to be used as planting material were collected from the seed source garden of PT Socfin Indonesia. The study was carried out from January to February 2019, using a non-factorial randomized block design. The morphological characters observed were tapped root length, shoot height, the increased rate of taproot length, shoot height increase rate, ratio of taproot length, and shoot height. Data were analyzed using analysis of variance, discriminant, and drought stress sensitivity index. The results showed that the addition of PEG 6000 in planting media in vitro significantly influenced the character of the rate of increase of taproot length. The sensitivity index of taproot increase rate and the ratio of taproot length and shoot height was moderate at 7.5% levely contrast, the addition of PEG 6000 in planting media in vitro did not significantly impact it. The present study suggested that the rate of increase of taproot length was a distinguishing character showing the initial tolerance level of the GT1 seedlings to drought.